Klinische Sportmedizin - Heblich F; Gröbel H; Hauptmann M (Deutsche Zeitschrift für Sportmedizin, 2018)
Background: The mandatory medical fitness examinations of firefighters and occupational divers with ergometry are important, but in Germany they are based on two criticized models, Reiterers model and the PWC-model.Aim: We examine the weaknesses of these models and offer alternatives. Besides, we discuss other problems of the fitness examinations.Methods: In bicycle ergometry tests with 8583 firefighters we collected data concerning age, mass and final achievements and developed mathematical models that allow us to estimate the Median of the final achievement from age and mass.The special relevance here is that our models are based on data of firefighters and are therefore better suited as basis of medical fitness tests in contrast to Reiterers model which was conceived for another purpose.Results: Reiterers model is based on measurements with less-fit test persons. As expected, on average it underestimates the achievements. The structure is clearly not as precise as our models. The PWC model is even less precise and is inclined to overestimate the achievements. Our algorithm Pincremental well describes the physical fitness of firefighters and can be used to construct reference models, based on gender, form of ergometry and failure rate.Conclusion: We recommend the use of new models for medical fitness examinations. When using a bicycle ergometer, a gradual increase protocol with steeper gradient instead of the present increment should come into use. The fitness examinations of firefighters should be based more on data from the job and contain job-specific forms of ergometry, at least in part.KEY WORDS: Bicycle Ergometry, Firefighters, Fitness Tests, Cardiopulmonary Performance